(untitled) - Gregson, Geoffrey (Business Expert Press, 2014)
Ebook from IG Library ; So many business ventures today are looking to attract external financing, with an emphasis on business angel investment. Inside this text, the author incorporates the views of business angels, venture capitalists, entrepreneurs, and legal advisors; draws upon the latest academic thinking on financing new ventures and provides comparisons between business angel and venture capital investing to further inform the reader. The concepts, principles, and guidelines presented in this book, can help you and any entrepreneur, business support agency, business student, and others interested in raising external investment and in developing an investable business. The book is organised into seven chapters covering key topics; fundamental concepts of entrepreneurial venturing and entrepreneurial finance; market conditions from which investable businesses emerge (with guidelines for building an investable business case); the investment process; deal negotiations; the relationship between entrepreneur and investor post investment; and recent trends affecting how entrepreneurs raise finance that include strategic exits, super angels and the emergence of crowdfunding.
Keywords: Tài chính doanh nghiệp; Tài chính kinh doanh; Business finance